Factors Affecting The Income Level of The Fishing Community are Reviewed from An Islamic Perspective - Daulay, Khairani Andini; Armayani, Reni Ria; Nasution, Juliana (Yayasan Ilomata, 2025)
This research is motivated by the fact that the majority of the population in Labuhanbilik Village works as fishermen with a relatively low level of community welfare, and several factors such as working capital, work experience, education level and catch on fishermen's income are still inadequate because if the supporting factors are not met, the fishermen's income will decrease. This study aims to find out and explain the influence of working capital, experience, education level, and catch on fishermen's income in Labuhanbilik Village, Central Panai District, whether it has a significant effect partially or simultaneously, and which variable is more dominant. The research method used in this study is descriptive quantitative using data collection techniques such as questionnaires, interviews, and observation. Data analysis techniques to answer hypotheses use multiple linear regression analysis techniques. The study results show that working capital, work experience, and catch per day significantly affect monthly income. In contrast, education level does not affect monthly income. And the variable for Fishermen's Income in Labuhanbilik Village is the working capital variable with a calculated T value of 2,792 with a significance value of 0.008.